Guds omskiftelighed eller Guds bevægelighed? - Gregersen, Niels Henrik (Dansk Teologisk Tidsskrift, 2011)
This review argues that there are two incompatible lines of argument in Niels Grønkjær’s interesting book on Den nye Gud [The New God: After Fundamentalism and Atheism]. The first line suggests a purely temporal understanding of the Trinity: The Father gives up his power, then both Son and Father die on the cross, while only the Spirit persists in the human community of love. The second line of thought represents an Augustinian model of Trinity, reformulated via Hegel. It seems that only the second line can fulfill the author’s intentions.